FUNGSI DOA DI MEDIA SOSIAL: STUDI PRAGMATIK PADA KOMENTAR YOUTUBE - Roby Aji (Politeknik Negeri Jakarta, 2023)
Communication through digital media has a broad impact on religious life. Posting prayers on an online platform is one of the issues that have arisen. However, no research from a pragmatic perspective has been found that specifically addresses this phenomenon. Therefore, this research was conducted to (1) describe the strategies of speech acts in prayer on YouTube comments, and (2) describe their functions in the social context. This research is a qualitative-descriptive study. The data were obtained from two videos entitled